The Oxford handbook of emotion, social cognition, and problem solving in adulthood - Verhaeghen, Paul; Hertzog, C. K. (Christopher K.), 1952- (Oxford library of psychology., 2014)
Oxford Handbooks offer authoritative and up-to-date review of original research in a particular subject area. Specially commissioned chapters from leading figures in the discipline give critical examinations of the progress and direction of debates as well as a foundation for future research. Oxford Handbooks provide scholars and graduate students with compelling new perspectives upon a wide range of subjects in the hummunities. Social Sciences and Sciences.